Getting to Know Vue.js : learn to build single page applications in Vue from scratch - Nelson, Brett (Apress, 2018)
Learn how to render lists of items without repeating your code structure and how to work with conditional rendering items and event handling. Containing all you need to know to get started with Vue.js, this book will take you through using build tools (transpile to ES5), creating custom components, state management, and routers. With Getting to Know Vue.js, you'll see how to combine reusable code with custom components, allowing you to create snippets of reusable code to suit your specific business needs. You'll also explore how to use Single File Components and the Vue.js Command Line Interface (CLI) to build components in a single file and add in build tools as you see fit. Getting started with a new Single Page Application (SPA) JavaScript framework can be an overwhelming task, but Vue.js makes this daunting task simple and easy to learn, allowing you to start implementing business needs with just a script reference to the library and the custom JavaScript required for your use case. Starting with a little reference and a handful of lines of custom JavaScript, you will have a complete Single Page Application before you know it.